Definicije i nazivlje elektroničke građe : s pregledom nazivlja u Vjesniku bibliotekara Hrvatske - Klarin Zadravec, Sofija (2007)
The paper gives a review of definitions and terms used for electronic resources in ISBSs and discusses the background for their revision. Frequently used terms and definitions in other relevant standards and library literature are also discussed. The author gives a brief report of the use and relations of the explored terms. Croatian electronic resources terminology is illustrated by examples from the indexes and articles of the journal Vjesnikbibliotekara Hrvatske. The author points at the terminological problems in translation and emphasizes that a new terminology must be adopted
Bibliografske bilješke uz tekst ; bibliografija: 47 jed
Summary
Keywords: Elektronički izvori -- Nazivlje